Nursing of a patient with knee osteoarthritis treated by Traditional Chinese Medicine ointment (中药膏摩治疗膝关节骨性关节炎1例的护理体会) - WANG Ruofei (王若飞); ZHANG Pin (张聘); DONG Yuxia (董玉霞); LIU Jie (刘洁) (中西医结合护理)
This article summarized the nursing management for a patient with knee osteoarthritis treated with Traditional Chinese Medicine(TCM) ointment. The Chinese herbal medicine and acupoints were selected by syndrome differentiation. In addition to daily life support, psychological care and health education, TCM ointment external application combined with acupoints massage were carried out to relieve the pain and improve the knee joint function of the patient. (本文总结1例膝关节骨性关节炎患者运用中药膏摩治疗的护理体会, 通过辨证分型, 选取对症的中药和穴位, 施以中药膏敷和穴位按摩, 并做好生活指导、心理干预和健康宣教等护理措施, 有助于缓解患者关节疼痛, 改善膝关节功能。)